2017
DOI: 10.1001/jamainternmed.2016.8263
|View full text |Cite
|
Sign up to set email alerts
|

Cost of Joint Replacement Using Bundled Payment Models

Abstract: IMPORTANCE Medicare launched the mandatory Comprehensive Care for Joint Replacement bundled payment model in 67 urban areas for approximately 800 hospitals following its experience in the voluntary Acute Care Episodes (ACE) and Bundled Payments for Care Improvement (BPCI) demonstration projects. Little information from ACE and BPCI exists to guide hospitals in redesigning care for mandatory joint replacement bundles. OBJECTIVE To analyze changes in quality, internal hospital costs, and postacute care (PAC) spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
190
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 282 publications
(201 citation statements)
references
References 16 publications
10
190
1
Order By: Relevance
“…This finding is consistent with recent work that points to post-acute care as a potential culprit for waste in the US system (Navathe et al 2017; Baicker and Chernew 2017; Newhouse and Garber 2013). Such care is a major contributing factor to residual geographic variation in healthcare spending among the over-65 population (Newhouse and Garber 2013; Newhouse, Garber, and Graham 2013), a result found for the under-65 population as well (Franzini et al 2014).…”
supporting
confidence: 92%
“…This finding is consistent with recent work that points to post-acute care as a potential culprit for waste in the US system (Navathe et al 2017; Baicker and Chernew 2017; Newhouse and Garber 2013). Such care is a major contributing factor to residual geographic variation in healthcare spending among the over-65 population (Newhouse and Garber 2013; Newhouse, Garber, and Graham 2013), a result found for the under-65 population as well (Franzini et al 2014).…”
supporting
confidence: 92%
“…Our study adds to prior work examining BPCI and the related Comprehensive Care for Joint Replacement (CJR) program. Prior single‐center studies of joint replacement under BPCI have suggested that savings accrue from reducing high‐cost institutional PAC care . Dummit et al found evidence of modest savings among BPCI participants compared to nonparticipants, as well as reduction in institutional PAC use and duration, and Finkelstein et al found similar patterns in CJR .…”
Section: Discussionmentioning
confidence: 97%
“…This result is partially driven by the significant upfront investments in care redesign and the inability to recover these costs for low‐volume hospitals. However, for commoditized procedures like LEJR, significant cost reductions can be obtained through interventions which do not require potentially expensive care redesign efforts such as reducing implant costs or avoiding higher cost postacute care . Our findings provide information that could enhance the tailoring of care management pathways to reduce costs for patients more likely to incur greater costs.…”
Section: Discussionmentioning
confidence: 84%